An Italian Renaissance Gate for the Khan: Visual Culture in Early Modern Crimea - Nicole Kançal-Ferrari (Крымское историческое обозрение)
The article is a translation from English of the scientific work of the Turkish historian Nikole Kançal Ferrari: “An Italian Renaissance Gate for the Khan: Visual culture in Early Modern Crimea”. The article deals with the issue of foundation and identification of the author of the Iron Door (Demir Kapu) project in Backchisarai. The article also considers the question of the original location and date of installation of the project. This is rather difficult task due to the intensive restoration works and replacement of many decayed decorative components of the portal. The accurate analysis of the original appearance of the monument is almost impossible. In this regard, the analysis and research of the other sources is carried out except for the gates of the Topkapi Palace in Istanbul and the surviving inscriptions of the Crimean Khanate.